735. Severity and Healthcare Costs of Respiratory Syncytial Virus Hospitalizations in US Preterm Infants Born at 29–34 Weeks Gestation: 2014–2016. (26th November 2018) - Goldstein, Mitchell; Krilov, Leonard R; Fergie, Jaime; Ambrose, Christopher S; Wade, Sally; Kong, Amanda; Brannman, Lance
Abstract: Background: In 2014, the American Academy of Pediatrics recommended against the use of respiratory syncytial virus (RSV) immunoprophylaxis in infants 29–34 weeks gestational age (wGA) at birth without chronic lung disease/bronchopulmonary dysplasia (CLD/BPD) or congenital heart disease (CHD). To inform discussions of the clinical and economic value of RSV immunoprophylaxis in these infants, we compared RSV hospitalization (RSVH) severity and costs incurred by infants hospitalized from 2014–2016 at <6 months chronologic age (CA) for two groups: 29–34 wGA infants without CLD/BPD or CHD and term infants (≥37 wGA) without major health problems. Methods: Births were identified in the MarketScan Commercial (COM) and Multistate Medicaid (MED) databases. Term and 29–34 wGA infants without CLD/BPD or CHD were selected using DRG and ICD-9/10-CM diagnosis codes. RSVH occurring from Julu 1, 2014 to June 30, 2016 while infants were <6 months CA (the period of highest RSVH incidence) were identified by ICD-9/10-CM diagnosis codes. Severity measures were length of stay (LOS) in days, intensive care unit (ICU) admissions, and healthcare costs (paid amounts on reimbursed hospital claims in 2016 US). Comparisons between term and 29–34 wGA infants were made with t -tests and chi-squared tests. Results: There were 1, 114 RSVH in the COM data and 3, 167 RSVH in the MED data during the study period. Mean LOS was longer for 29–34 wGA infants than term infants for each age category ( P < 0.05) and tended to be longer for MED infants vs. COM infants (Figure 1). Thirty-eight percent of COM 29–34 wGA infants and 52% of MED 29–34 wGA infants hospitalized for RSV at <3 months CA were admitted to the ICU (Figure 2). RSVH costs for 29–34 wGA infants were greater than term RSVH costs for each age category ( P < 0.05) and were greatest among 29–34 wGA infants hospitalized at <3 months CA: 41, 104 for 29–34 wGA COM infants and 24, 049 for 29–34 wGA MED infants (Figure 3). Conclusion: RSVH severity and costs were significantly higher for 29–34 wGA infants without CLD/BPD or CHD relative to term infants. Infants hospitalized at <3 months CA experienced the most severe hospitalizations and incurred the highest costs. This study was funded by AstraZeneca. Disclosures: M. Goldstein, AstraZeneca/MedImmune: Consultant, Research grant and Research support. L. R. Krilov, AstraZeneca/MedImmune: Consultant, Research grant and Research support. J. Fergie, AstraZeneca/MedImmune: Consultant and Speaker's Bureau, Research grant and Research support. C. S. Ambrose, AstraZeneca: Employee, Salary and Stocks. S. Wade, Wade Outcomes Research and Consulting: Employee, Salary. A. Kong, Truven Health Analytics, an IBM Company: Employee, Salary. L. Brannman, AstraZeneca: Employee, Salary and Stocks.